The Qatar 2022 World Cup warm-up: Football goal-scoring evolution in the last 14 FIFA World Cups (1966–2018) - Mićović, Branimir; Leontijević, Bojan; Dopsaj, Milivoj; Janković, Aleksandar; Milanović, Zoran; Garcia Ramos, Amador (Frontiers in Psychology, 2023)
The aim of this study was to elucidate pattern of attacking actions leading up to goal scoring during the 14 FIFA World Cups from 1966 to 2018. The study analysed 1881 goals scored during a total of 732 matches. We employed observational methodology design. The video material for the analysis was obtained from the website https://footballia.net, which contains videos of all of the previous 14 FIFA World Cup matches. Each goal scoring action was captured in a video clip using the iMovie software. Before goal analysis began, it was developed the observing protocol, in which data related to selected variables, by system of notation, was entered after reviewing each individual goal scoring action. A statistically significant trend (p<0.05) from 1966 to 2018 was identified towards a higher relative frequency of goals scored from set play and collective actions from open play. The Chi-square did not reveal significant differences in the frequency of goal scoring patterns and goal-scoring zones. The results also revealed that the majority of goals were scored between the 76th and 90th minutes of a match (22.7%), from open play (70.5%), inside the penalty area (54.7%), one touch finishing (62.5%), and collective attacks in open play (55.8%). These findings may provide a possible strategic direction for improving goal-scoring performance in football, as well as practical implementation in World Cup tournament preparation.